Analysis of Compressive Strength Test Characteristics of Concrete Using Fine Aggregates from Joubela Village and Coarse Aggregates from Sabala Village - Ismul Sibua; Joni Hermanto; Muhammad Usamah (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
Utilizing local materials in construction is a strategic approach to reduce development costs, especially in regions with limited logistical access. This study aims to assess the compressive strength characteristics of concrete made from local aggregates: fine aggregate from Joubela Village and coarse aggregate from Sabala Village. This approach is expected to provide an economical and efficient alternative for regional infrastructure development. The methodology involved testing the physical properties of the aggregates and designing concrete mixes according to SNI 03-2834-2000 standards. Results showed that the fine aggregate from Joubela has a specific gravity of 1.97 g/cm³, a fineness modulus of 2.96% (zone 3), a unit weight of 1.69 g/cm³, clay content of 2.50%, and moisture content of 4.60%. Meanwhile, the coarse aggregate from Sabala has a specific gravity of 2.58 g/cm³, clay content of 0.27%, moisture content of 1.97%, fineness modulus of 7.52%, loose unit weight of 1.60 g/cm³, and compacted unit weight of 1.66 g/cm³. Both materials meet the quality requirements for concrete aggregates. Based on compressive tests with a mix design of 51.5 kg cement, 24.7 liters water, 61.1 kg fine aggregate, and 157.7 kg coarse aggregate, an average compressive strength of 23.95 MPa was obtained after 28 days, exceeding the target of 21.7 MPa. Therefore, the combination of aggregates from both villages shows high potential for use in structural concrete. Future research should include cost-efficiency analysis and durability testing in aggressive environments to ensure material sustainability.